SIMULASI 3 DIMENSI DISTRIBUSI PANAS PLAT KNALPOT MOBIL UNTUK ELEMEN TERMOELEKTRIK - Adli, Wildan; Tambunan, Walfred; Umar, Lazuardi (Komunikasi Fisika Indonesia, 2016)
This study simulates the distribution of heat in the conductor plate micro energy generation based module Thermoelectric Generator (TEG) type 40-40-10 / 100 to optimize the absorption of heat from the vehicle exhaust waste heat. The module has a maximum operating temperature of 423K. The modeling is done using MATLAB with a modified diffusion equation by application of 900K of temperature as boundary condition on the surface of the base plate which is in contact with the heat source. The plate with aluminum material modeled in varies form of solid, hollow, hollow gitter, hollow heatsink, with dimensions of 110mm long, 60mm wide, 30mm thick base and 30mm thick bulge. The best temperature drop obtained for ÎT = 178,67K (19.85%) produced by the shape of a hollow heatsink plate. The resulting temperature of this model is then lowered back with varying types of material such as aluminum, copper, iron, and stainless steel, as well as by varying the number of TEG array that is 1 to 4-arrays, each array consisting of two modules. Drop in temperature that comes closest to the maximum TEG operating temperature is a drop in temperature that generates the final temperature of 402K, which comes from hollow-with-heatsink stainless steel plate with 50mm of thick and 4-arrays formation.